Investigation of air pollution and health effects as per dose-response functions and prioritizing responsibility of pollutants based on Multi-Criteria Decision Making computations: A case study - Mohammad Gheibi; Benyamin chahkandi; Zahra Kian; Amir Takhtravan; Reza Aghlmand (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
With the growth of industrialization and urbanization in megacities, some emerging disasters occur such as air pollution mortality, increasing cancer risks, decreasing life expectancy, descending prosperity, and Human Development Indexes (HDI). In addition, with the raising population of cities, the quantity and quality of air pollutions are increased based on vehicle application rate, industrial activities, agricultural efforts and etc. In this research, with the application of Dose-Response Functions in air pollution, some parameters such as chronic disease-based mortality, life expectancy reduction based on chronic and acute effects, and ozone gas health risks are computed in a case study of Mashhad city, Iran. The outcomes have illustrated the life expectancy is reduced in a case study around 8.22 and 8.51 years for men and women, respectively. Plus, the results of statistical health scrutinizing have demonstrated that the mortality of chronic effects based on air pollution emissions is calculated around 20 percentages in the case study. Likewise, with the application of two different methods in Multi-Criteria Decision Making (MCDM) containing Analytic Hierarchy Process (AHP) and ELimination Et Choice Translating Reality (ELECTRE) the responsibility of each pollution is determined. As per the mentioned computations, Particle Matter 2.5 (PM2.5) has the most role in increasing the health risk of air pollution in Mashhad City, Iran.